MONITORING EVALUATION FOR IMPLEMENTATION REGIONAL REGULATION NO 5 YEAR 2008 ABOVE SMOKE- FREE AREA (SFA) AND SMOKE- RESTRICTED AREA (SRA) TO PUBLIC PLACE IN SURABAYA - Kurnia D Artanti1, Santi Martini1, Kusuma S Lestari2 (MTCC, John Hopkins n The Union, 2015)
Background: Regional regulations regarding Smoke Free Areas (SFA) and Smoke Restricted Areas (SRA) have been implemented in Surabaya since 2009. SFA is an area where individuals who is prohibited to conduct activities related smoking like as: producing or making cigarettes; sell cigarettes; organized cigarette advertising; promoting cigarettes and cigarette use; and SRA is an area where individuals are permited to smoke in limited areas. The management must provide a designated smoking room and put â€œ No smokingâ€ signage in other areas. After 5 years, it seems that implementation of the policy is still weak. Previous study showed 75.4 % facilities in SFA and SRA have yet to instal no-smoking signage in accordance with Regional Regulation No. 5 Surabaya year 2008 (Santi, 2011). The results of the survey of Smoking-Restricted Areas (SRA) in 2012 showed that people are still found to be smoking inside the building, Ashtray, cigarettes and cigarette sellers were found in the smoking area (DKK, 2013).. The aim of the study was to monitor and evaluate implementation of the Regional Regulation No. 5 of 2008 Surabaya on SRAand SFA in public and work places (malls, parks, hotel, restaurant and tranportation). Methods: This was a crossâ€“sectional study and used both quantitative and qualitative approaches. A survey of 200 work and public places that were categorized as Smoking Restricted Areas and Smoking Free Areas under the Regulation were conducted. Cluster Random Sampling was used based on different areas of Surabaya (East, West, Center, North, and South). Data collection was done by an observation check list and semi-structured interview with open-ended questionnaire was used with management authority and consumers at these public places. Results: The overall implementation of the Surabaya City Regional Regulation No. 5 of 2008 is still very weak due to many violations in almost all observed indicators. Most violations were despite the presence of signage that indicated SFA and SRA at public places, there were smoking rooms provided that is not in accordance with the Regional Regulation No. 5 of 2008. The others observed indicator was Founded smoker, the smell cigarette smoke, Astrays and lighter. SEED RESEARCH GRANT 2015 THE 2ND INDONESIA TOBACCO CONTROL CONVERENCE AND CAPACITY BUILDING PROGRAM 2015 101 Conclusions: To increase the effectiveness of the implementation, the Regulation needs to be disseminated regularly and continuously among local government officials and managers of public facilities and efforts made to build public awareness and more stringent enforcement practices. Keywords : SFA, SRA, Implementation, Monitoring, Evaluation.